Impact of soil microorganisms on weed biology and ecology - Boyetchko, S.M. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1996)
While weed populations have traditionally been controlled by chemical and cultural methods, inundative biological control with microbial agents offers an additional strategy for managing weeds. Foliar pathogens have long been sought after as potential biocontrol agents, but rhizosphere microorganisms and their influence on weed growth and development have been ignored until recently. Rhizosphere soil is replete with a variety of microorganisms such as rhizobacteria, pathogenic soil-borne fungi, and arbuscular mycorrhizal fungi, all of which have a direct or indirect impact on weeds and their competitive ability. In some cases, specific microbes have a detrimental effect on the weeds and can be exploited as biological control agents. The ubiquitous mycorrhizal fungi are beneficial symbionts that can impart a competitive ad vantage to their plant hosts, particularly if mycorrhizal dependency is exhibited in weeds as opposed to crops. It may be possible to exploit various soil microbes by directly or indirectly reducing weed competition and tipping the competitive advantage in favor of the crop. However, information available on microbial/weed/crop relationships is limited and research efforts are required to explore the use of soil microorganisms as another weed management tool.